DDS-XRCE Standard Performance Evaluation of Different Communication Scenarios in IoT Technologies - Solpan, Sevval; Kucuk, Kerem (EAI Endorsed Transactions on Internet of Things, 2022)
Although the increasing number of technological products brings many solutions for Internet of Things (IoT) applications, it also causes some drawbacks, such as whether the product in question would run accordingly to a system structured to enable high-performance like Data Distribution Service (DDS). Therefore, the capabilities of the products must be defined to say that they are compatible enough. This paper aims to evaluate the performance of the DDS-XRCE standard while observing its working mechanism. As test scenarios, we benefit from three DDS-XRCE deployments that occurred due to the kind of receiver and sender, the path that packets follow, and the protocols used. Test conditions were set by switching stream modes, transport profiles, and limiting packet deliveries. We obtained the test environment by creating the DDS and DDS-XRCE objects using several eProsima implementations and tools for the standards. We monitored the network messages in two ways: 1) Using multiple Gnome Terminator terminals for observation via the human eye during testing. 2) Using Wireshark to save the information of the packets for further examination. We conducted 36 experiments focusing on latency, throughput, and packet loss. As a result of our study, the DDS-XRCE standard is deemed suitable for Internet of Things applications.